Conformational dynamics of the rotary subunit F in the A3B3DF complex of Methanosarcina mazei Gö1 A-ATP synthase monitored by single-molecule FRET - Singh, Dhirendra (2017)
In archaea the A1AO ATP synthase uses a transmembrane electrochemical potential to generate ATP, while the soluble A1 domain (subunits A3B3DF) alone can hydrolyse ATP. The three nucleotide-binding AB pairs form a barrel-like structure with a central orifice that hosts the rotating central stalk subunits DF. ATP binding, hydrolysis and product release cause a conformational change inside the A:B-interface, which enforces the rotation of subunits DF. Recently, we reported that subunit F is a stimulator of ATPase activity. Here, we investigated the nucleotide-dependent conformational changes of subunit F relative to subunit D during ATP hydrolysis in the A3B3DF complex of the Methanosarcina mazei Gö1 A-ATP synthase using single-molecule Förster resonance energy transfer. We found two conformations for subunit F during ATP hydrolysis.